Effect of resistance exercise in increasing enzyme superoxide dismutase and glutathione peroxidase in skeletal muscle: A literature review - Liowina Adlin Hokky; Ditha Subagiantara; Ellisa Koeswanto; Indira Juhanna; Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2024)
Abstract Background: The skeletal muscles produce reactive oxygen species (ROS) during contraction. Exercise such as endurance training has been shown to increase the activities of several antioxidant enzymes. It is difficult to investigate resistance training due to the complex protocol to make the model of resistance exercise. In this review, we would like to create a concise explanation of the role of resistance training in increasing the activity of the antioxidant enzyme. Methods: We performed literature searching in several online databases such as PubMed, EMBASE, CENTRAL, and Google Scholar. We performed searching using keywords (resistance training) AND (antioxidant enzyme) to find eligible literature. We create a narrative review to discuss about the role of resistance training to antioxidant enzyme. Discussion: The primary free radical that is produced by the skeletal muscle are O2•? and nitric oxide (NO). However, the contraction of the skeletal muscle also increases the activities of antioxidant enzymes. There are five key antioxidant enzymes in the skeletal muscle, which are including superoxide dismutase, glutathione peroxidase, catalase, peroxiredoxins, and thioredoxins. There is a network between PGC-1? and ROS, where ROS regulates PGC-1? production, and PGC-1? regulates ROS production during resistance exercise. The PGC-1? plays a role in the regulation of the antioxidant enzyme, especially in the sequence of MnSOD and glutathione system. Conclusion: Resistance training increases the expression of antioxidant enzymes, especially SOD and glutathione peroxidase. Keywords: antioxidant; enzyme; resistance training